2015
DOI: 10.1111/vec.12303
|View full text |Cite
|
Sign up to set email alerts
|

Administration of fenoldopam in critically ill small animal patients with acute kidney injury: 28 dogs and 34 cats (2008–2012)

Abstract: In this study of patients with AKI, fenoldopam administration at 0.8 μg/kg/min in dogs and 0.5 μg/kg/min in cats appeared relatively safe but was not associated with improvement in survival to discharge, length of hospital stay, or improvement in renal biochemical parameters when compared to patients with AKI not receiving fenoldopam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…To prevent hypotension, fenoldopam administration was initiated 4 hours PP, after hydration status and hypovolemia had been corrected. Hypotension episodes after fenoldopam initiation were uncommon, and with aggressive IV fluid administration, it is quite safe at the currently administered dosage, in agreement with a previous pharmacokinetic study of fenoldopam in dogs, and others, in which fenoldopam administration was uncommonly (7%) associated with hypotension in dogs …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To prevent hypotension, fenoldopam administration was initiated 4 hours PP, after hydration status and hypovolemia had been corrected. Hypotension episodes after fenoldopam initiation were uncommon, and with aggressive IV fluid administration, it is quite safe at the currently administered dosage, in agreement with a previous pharmacokinetic study of fenoldopam in dogs, and others, in which fenoldopam administration was uncommonly (7%) associated with hypotension in dogs …”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of fenoldopam as preventive therapy for AKI in animals at high risk for AKI has not been evaluated in a controlled study, and evidence regarding its efficacy in animals with AKI is limited. In a retrospective study of dogs and cats with AKI, fenoldopam had no beneficial effects, but its effects on UP, GFR, and solute excretion were not evaluated …”
Section: Introductionmentioning
confidence: 99%
“…The altered renal perfusion, tubular epithelial cell dysfunction, and altered tubular flow rate through the nephron observed in states of renal injury preclude simple extrapolation of the results of our study to a dog with AKI, because it cannot be assumed that a diseased kidney would respond similarly to fenoldopam. A recent retrospective study in dogs and cats with AKI indicated that fenoldopam administration resulted in no improvement in survival to discharge, duration of hospital stay, or renal biochemical variables when compared with AKI patients that did not receive the drug . The retrospective nature of this study failed to control for other concurrent treatments as well as the severity of AKI, and no objective measures of GFR or sodium excretion were performed.…”
Section: Discussionmentioning
confidence: 89%
“…A recent retrospective study in dogs and cats with AKI indicated that fenoldopam administration resulted in no improvement in survival to discharge, duration of hospital stay, or renal biochemical variables when compared with AKI patients that did not receive the drug. 24 The retrospective nature of this study failed to control for other concurrent treatments as well as the severity of AKI, and no objective measures of GFR or sodium excretion were performed. Prospective controlled clinical studies are warranted to assess the effect of fenoldopam on dogs with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dopamine is controversial, and it no longer is used routinely in human patients . Recently, fenoldopam has been evaluated in human and veterinary patients with conflicting results …”
Section: Introductionmentioning
confidence: 99%